Does Access to Health Care Mitigate Environmental Damages? - Jamie Mullins; Corey White (Institute of Labor Economics (IZA), 2019)
Differential access to health care is commonly cited as a source of heterogeneity in the health effects of environmental exposure, yet little causal evidence exists to support such claims. We test this hypothesis by utilizing exogenous variation in both access to health care and environmental exposure. Variation in access to care is derived from the roll-out of Community Health Centers (CHCs) across US counties in the 1960s and 1970s, and variation in environmental exposure comes from random year-to-year fluctuations in ambi-ent temperature within counties. We find that the provision of primary care through CHCs mitigates the relationship between heat and mortality by approximately 15%. Our results suggest that differential access to health care does contribute to observed heterogeneity in environmental health damages, and that improving access to primary care may be a useful means of mitigating harm from a warming climate.
Keywords: I10; I14; I18; Q50; Q52; Q54; Q58; 330; health care; access; climate; temperature; environment